2003
DOI: 10.1260/026309203323022580
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Human Body Surface Vibrations Induced by Complex Low-Frequency Noise Composed of Two Pure Tones

Abstract: To clarify the mechanical responses of the human body to airborne vibrations, six male subjects were exposed to eight kinds of low-frequency noise stimuli: airborne white noise, two pure tones (31.5 and 50 Hz), and five complex noises composed of pure tones. The vibrations induced on the body surface were measured at five locations: the forehead, the right and left anterior chest, and the right and left anterior abdomen. It was found that the vibration acceleration levels of both the 31.5-and 50-Hz components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…When a person is exposed to high-level low-frequency noise, actual body vibration is induced [19][20][21] . The levels of this vibration (noise-induced vibration) are not especially high, but we found that noise-induced vibrations measured on the chest or abdomen were closely related to vibratory sensation perceived in each corresponding part of the body 22) .…”
Section: Introductionmentioning
confidence: 99%
“…When a person is exposed to high-level low-frequency noise, actual body vibration is induced [19][20][21] . The levels of this vibration (noise-induced vibration) are not especially high, but we found that noise-induced vibrations measured on the chest or abdomen were closely related to vibratory sensation perceived in each corresponding part of the body 22) .…”
Section: Introductionmentioning
confidence: 99%